2016
DOI: 10.1159/000447008
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Usefulness of Claudin-3 and Claudin-4 for Immunocytochemical Differentiation between Metastatic Adenocarcinoma Cells and Reactive Mesothelial Cells in Effusion Cell Blocks

Abstract: Objective: Claudin-3 and claudin-4 have recently been reported as promising targets for the detection and diagnosis of cancer. This study was designed to evaluate the diagnostic value of claudin-3 and claudin-4 immunoreactivity to distinguish metastatic adenocarcinoma cells (MAC) from reactive mesothelial cells (RMC) in effusions. Study Design: Claudin-3 and claudin-4 immunocytochemical staining was performed on 234 cell block specimens, including 194 malignant effusions with MAC and 40 benign effusions with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(88 reference statements)
2
13
0
Order By: Relevance
“…Lonardi et al also described intra‐cytoplasmic dot staining in mesothelial and inflammatory cells, which they considered non‐specific, while Jo et al reported weak cytoplasmic staining in some mesotheliomas. By contrast, others have described membranous staining with Claudin‐4 in around a quarter of cases of reactive mesothelium. We found the pattern of cytoplasmic staining observed in mesothelial cells easy to discriminate from the linear membrane staining observed in the majority of adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Lonardi et al also described intra‐cytoplasmic dot staining in mesothelial and inflammatory cells, which they considered non‐specific, while Jo et al reported weak cytoplasmic staining in some mesotheliomas. By contrast, others have described membranous staining with Claudin‐4 in around a quarter of cases of reactive mesothelium. We found the pattern of cytoplasmic staining observed in mesothelial cells easy to discriminate from the linear membrane staining observed in the majority of adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 84%
“…There is less concordance in published results for the expression of claudin‐4 by mesothelial cells. Some authors have found no reactivity in mesothelial cells, whereas Kim et al reported weak membranous staining in 27.5% of reactive mesothelial cases. Soini et al also reported reactivity in a series of surgical specimens including 24 adenocarcinomas (100% positive) and 35 mesotheliomas (23%).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The markers used to identify malignant epithelial cells were MOC-31, Claudin 4 and IMP3, but several other adenocarcinomas markers have been used to distinguish malignant epithelial cells from mesothelial cells such as B72.3, CEA and Ber-EP4 (30)(31)(32)(33)(34). Besides, some primary site markers of adenocarcinoma can also contribute to distinction between mesothelial and epithelial malignant cells such as estrogen receptor, progesterone receptor, GATA3, mammoglobin, GCPd15 for breast; Napsin-A and TTF-1 for lung; CdX-2, villin, SATB2 for gastrointestinal tract; PSA for prostate; PAX8, HBME and estrogen receptor for ovary; Cd10 and PAX 8 for kidney; hepatocyte-specific antigen for liver.…”
Section: Discussionmentioning
confidence: 99%